Development of physical culture and sports in Krements and Volyn between the military period during the activity of Julian Kozlowski, professor of Kremenets Lyceum - Lubov Plevachuk; Igor Grygus; Eligiusz Małolepszy (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
This article describes Professor Julian Kozlowski's activity at Kremenets Lyceum. Being an excellent specialist, he raised physical culture and sports to a new level, which made Kremenets Lyceum one of the best sports centers in Volyn. Here it is shown the importance of innovations, including the Dalton system, implemented at physical education classes in Kremenets Lyceum. Due to Julian Kozlowski"s persistence, there were introduced mass sports tests for Ski Distinction and for State Sports Honors. Thanks to his initiative, ski jumping, swimming pool on the river Ikva, stadium, tennis courts were built here. He also participated in the construction of gliding sport school on Sokolyna Mountain near Kremenets. Professor Kozlowski gave lectures and courses to popularize physical culture and sports. He initiated various competitions and sports events. Julian Kozlowski was a great patriot of Poland.